Phylogeny of the genus Willemia (Collembola: Hypogastruridae) and biogeography of the W. buddenbrocki-group with description of a new species from Ivory Coast (western Africa) - Zon, Serge Déméango; Bedos, Anne; D’haese, Cyrille A. (Zootaxa, 2015)
Willemia tondoh sp. nov. from the Ivory Coast (western Africa) is described and illustrated. The new species is the 14th in the buddenbrocki-group and is defined with two large globular sensilla placed in a cavity and covered in part by tegumental fold on antennal segment IV, 7 chaetae on antennal segment I, postantennal organ with 9 vesicles, s-chaetae subcylindrical and acuminate on abdominal terga and chaetae a1 absent on abdominal sternum IV. A phylogeny for all the 46 species of the genus Willemia is proposed. Based on the phylogentic framework, the biogeography of the buddenbrocki-group is discussed. An identification key for all 46 known species of the genus is provided.